Peran Pemerintah dalam Pengembangan Pariwisata Era New Normal di Daerah Istimewa Yogyakarta melalui Aplikasi Visiting Jogja - Matheus Gratiano Mali (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to see the role of local government in the recovery and development of the tourism sector in the Special Region of Yogyakarta, in overcoming adversity due to the covid-19 pandemic and entering a new era of habits through the Visiting Jogja Apps program. This research is a qualitative descriptive study, collecting data obtained through interviews, observation and document analysis. The research was conducted at the Yogyakarta Special Region Tourism Office and a number of Associations in the Tourism Business Sector and also to the management of tourist sites in a number of regencies in the Special Region of Yogyakarta. The data analysis technique is carried out by means of data reduction, data presentation and verification or conclusions. The results of this study indicate that the Visiting Jogja Apps program has been programmed by the Special Region of Yogyakarta Tourism Office to adapt to pandemic conditions and become an alternative for carrying out tourism activities that adapt to health protocols, which are useful as support for tracing visitors or Covid-19 tracers However, the Visiting Jogja Apps program is still not optimal in carrying out supporting functions in tracing tourists who are confirmed to be positive for Covid, and there is no implementation rule or Standard Operating Procedure related to tracing it self.